Improving results for children and families : linking collaborative services with school reform efforts - Wang, Margaret C.; Boyd, William Lowe, 1935- (Emerald Publishing Limited : Information Age Pub., 2000)
Comprises three sections: emerging models for connecting community services reform; the impact of school- and community-based interventions and children's learning and development; and state and federal policies for building partnerships to improve outcomes for children and families.
Keywords: Educational innovations.; Community-based family services.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books